Macrophage-Mediated Bone Formation in Scaffolds Modified With MSC-Derived Extracellular Matrix Is Dependent on the Migration Inhibitory Factor Signaling Pathway - Deng, Moyuan; Tan, Jiulin; Dai, Qijie; Luo, Fei; Xu, Jianzhong (Frontiers in Cell and Developmental Biology, 2021)
The positive role of macrophages in the osteogenesis of mesenchymal stem cells (MSCs) has been a recent research focus. On the other hand, MSCs could carefully regulate the paracrine molecules derived from macrophages. Human umbilical cord mesenchymal stem cells (hucMSCs) can reduce the secretion of inflammatory factors from macrophages to improve injury healing. hucMSC-derived extracellular matrix (hucMSC-ECM) has the similar effect to hucMSCs, which could combat the inflammatory response of macrophages. Additionally, MSC-derived extracellular matrix also enhanced bone regeneration by inhibiting osteoclastic differentiation of monocyte/macrophage lineage. However, whether hucMSC-ECM could improve bone formation by guiding macrophage-induced osteogenic differentiation of MSCs is unknown. Here, we present decalcified bone scaffolds modified by hucMSC-derived extracellular matrix (DBM-ECM), which maintained multiple soluble cytokines from hucMSCs, including macrophage migration inhibitory factor (MIF). Compared with DBM, the DBM-ECM scaffolds induced bone formation in an improved heterotopic ossification model of severe combined immunodeficiency (SCID) mice in a macrophage-dependent manner. Macrophages cocultured with DBM-ECM expressed four osteoinductive cytokines (BMP2, FGF2, TGFβ3 and OSM), which were screened out by RNA sequencing and measured by qPCR and western blot. The conditioned medium from macrophages cocultured with DBM-ECM improved the osteogenic differentiation of hBMSCs. Furthermore, DBM-ECM activated CD74/CD44 (the typical MIF receptors) signal transduction in macrophages, including phosphorylation of P38 and dephosphorylation of c-jun. On the other side, the inhibitory effects of the DBM-ECM scaffolds with a deficient of MIF on osteogenesis in vitro and in vivo revealed that macrophage-mediated osteogenesis depended on MIF/CD74 signal transduction. The results of this study indicate that the coordinated crosstalk of macrophages and MSCs plays a key role on bone regeneration, with an emphasis on hucMSC-ECM constructing a macrophage-derived osteoinductive microenvironment.